2008
DOI: 10.1109/twc.2007.060842
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Channel Randomness on Coverage and Connectivity of Ad Hoc and Sensor Networks

Abstract: Abstract-In this paper, we first present an analytical procedure for the computation of the node isolation probability and coverage in an ad hoc network in the presence of channel randomness, with applications to shadowing and fading phenomena. These results are used to obtain an estimate of the connectivity features for very dense networks. Stochastic orderings are used to show the beneficial impact of lognormal shadowing and the negative impact of Rayleigh fading. The impact of SIMO/MISO and MIMO schemes is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 44 publications
6
83
0
1
Order By: Relevance
“…In all cases, ξ = 10 dB, and this corresponds to keeping the SINR threshold fixed. The figure suggests that the presence of lognormal shadowing improves the connectivity properties of the network, as predicted by the results in [24,25]. Furthermore, the link probability of success is monotonically increasing in the lognormal spread σ so that it can be concluded that, even though the presence of a deep fades impacts the received power on the link, it has globally a beneficial impact on the link SINR.…”
Section: The Log-normal Fading Link Modelmentioning
confidence: 57%
“…In all cases, ξ = 10 dB, and this corresponds to keeping the SINR threshold fixed. The figure suggests that the presence of lognormal shadowing improves the connectivity properties of the network, as predicted by the results in [24,25]. Furthermore, the link probability of success is monotonically increasing in the lognormal spread σ so that it can be concluded that, even though the presence of a deep fades impacts the received power on the link, it has globally a beneficial impact on the link SINR.…”
Section: The Log-normal Fading Link Modelmentioning
confidence: 57%
“…To begin with, with the introduction of mission-critical WSN applications, various researchers investigated the probability of full connectivity in ad-hoc networks to identify and prevent the occasions that a node is isolated from the rest of the network [3], [4]. One of the first works on this subject is [3] in which the connectivity and the impact of mobility in a large set of nodes is investigated.…”
Section: Related Workmentioning
confidence: 99%
“…One of the first works on this subject is [3] in which the connectivity and the impact of mobility in a large set of nodes is investigated. The same topic is extended in [4] by taking the channel randomness into account.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This parameter m is called the 'shape factor' of the Nakagami-m or the gamma distribution. The value results in the widespread Rayleigh-fading model [28], while values of m less than one correspond to fading more severe than Rayleigh fading and values of m greater than one correspond to fading less severe than Rayleigh fading. Where, X i, i = 1,2,………n are independent and identically distributed (i.i.d.)…”
Section: Nakagami-m Fading Modelmentioning
confidence: 99%